Early versus standard renal replacement therapy after left ventricular assist device implantation. Issue 10 (2nd August 2020) - Liu, Hua; Jeng, Eric; Demos, Daniel; Vilaro, Juan; Ahmed, Mustafa M.; Parker, Alex; Pinzon, James; Aranda, Juan; Beaver, Thomas M.; Arnaoutakis, George J.
Abstract: Objectives: Renal function may improve after left ventricular assist device (LVAD) implant, however, some patients develop postoperative acute kidney injury (AKI). Randomized trials showed benefit for early renal replacement therapy (RRT) in critically ill patients with AKI, but this practice has not been studied in LVAD patients. Methods: We performed a single‐center, retrospective cohort study of all adults (>18 years) who underwent LVAD placement from 1/2010 to 12/2018. We collected preoperative, hemodynamic, echocardiographic, intraoperative, and postoperative data. AKI was defined according to Kidney Disease: Improving Global Outcomes definition. Early (E) RRT was considered treatment at AKI stage II or below. Standard (S) RRT was considered treatment at AKI stage III. Outcomes and Kaplan‐Meier analysis were compared between groups. Results: A total of 184 patients were included (mean age 56.10 years, 81% males, 30.4% African‐American race). A total of 71 (38.6%) developed AKI and 17 (9.24%) needed RRT (11 E vs 6 S). A total of 11 remained hemodialysis‐dependent at discharge (5 [45.5%] in E vs 6 [100%] in S, P  = .043). There was a trend toward shorter intensive care unit stay and ventilation time in E group, and overall hospital stay was significantly less in the E group (48.18 ± 25.95 vs 94.00 ± 53.07 days, P  = .028). Thirty‐day mortality was similar between groups (E 18% vs S 16%, P  = .9), but there was a trend toward improved overall survival in the E group. Conclusion: This is the first study to examine early initiation of RRT after LVAD implant. Early RRT was associated with shorter hospital stay, lower need for permanent RRT, and a trend toward improved survival. This practice may provide significant cost savings and should be examined further.